The Role of Ethical Leadership in Strengthening Organizational Culture within Islamic Higher Education - Mukhlis Rahmatullah; Muhammad Irsyad Baitussalam (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2025)
This study explores the role of ethical leadership in strengthening organizational culture within Islamic higher education institutions. Ethical leadership, which emphasizes integrity, justice, accountability, and spiritual guidance, is essential for aligning academic excellence with Islamic values. Unlike secular institutions that often prioritize managerial efficiency, Islamic higher education requires leadership that functions not only as an administrative tool but also as a moral compass. Using a qualitative research design, data were collected through interviews, observations, and document analysis from academic leaders, administrators, and faculty members. The findings reveal that ethical leadership manifests in several key dimensions, including integrity and transparency, justice and fairness, spiritual and moral role modeling, accountability and stewardship, and community engagement. These dimensions significantly contribute to building trust, fostering collaboration, integrating academic and spiritual values, and strengthening institutional legitimacy. However, challenges such as limited financial resources, resistance to reforms, and pressures from globalization and government policies remain obstacles to implementation. The study concludes that ethical leadership serves as a fundamental driver of sustainable organizational culture in Islamic higher education. By embedding Islamic ethical principles into governance and institutional practices, leaders can balance global academic demands with faith-based commitments, ensuring both resilience and credibility.